Gene Therapy in Kidney Transplantation: Evidence of Efficacy and Future Directions - Li, Jiawei; Qi, Guisheng; Tu, Guowei; Yang, Cheng; Rong, Ruiming (Current Gene Therapy, 2017)
Allograft loss remains a severe clinical problem after kidney transplantation. The molecular mechanism of graft loss is a complex process involving T and/or B cell activation, inflammation responses, autophagy and apoptosis. Since these pathways are involved in immune responses in kidney transplant rejection, application of genetic interference to inhibit specific pathways could present an effective targeted gene therapy method. Recent studies have successfully attempted to use gene therapy to target the key molecules involved in immune responses during transplantation. This strategy has the potential to silence target genes associated with a variety of diseases, including those that trigger allograft loss following organ transplantation. In this review, we have discussed evidence of the clinical applicability of gene therapy in kidney transplantation based on known associations between kidney diseases and genes participating in the underlying mechanisms. The molecules contributing to immune responses and inflammatory injury are further highlighted as potential targets in future clinical therapy for renal transplantation.
Keywords: Gene therapy